Pengaruh Kualitas Pelayanan Terhadap Niat Ulang Dengan Menggunakan Produk Yang Lain Melalui Kepercayaan Nasabah Bank Syariah Mandiri Kantor Cabang Boulevard di Surabaya - Viandhy, Aditya Okta; Ratnasari, Ririn Tri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the effect of service quality on intention to re-use products other Bank Syariah Mandiri through the trust as an intervening variable.The method used is quantitative approach. Characteristics of the sample used is 30 customers of Bank Syariah Mandiri Boulevard branch in Surabaya who use a particular product. Sampling is using nonprobability sampling with purposive sampling procedure. The analytic technique is used path analysis or path analysis.The results showed that the quality of services significantly influence customer confidence in Bank Syariah Mandiri Boulevard in Surabaya. Other results show that trust significantly influence purchase intention by re-using the products of Bank Syariah Mandiri others. While service quality does not significantly influence customers purchase intention by re-using the products of Bank Syariah Mandiri others.Advice for Bank Syariah Mandiri branch in Surabaya Boulevard to always improve the quality of service to customers through good SERVQUAL and maintain the trust that exists between the customer and the bank to always be honest and maintain the trust that has been given by the customer to the bank. For further research can add variable customer loyalty in the Islamic perspective.